Optimalisasi radiografi gigi konvensional untuk membantu pemasangan implan gigi - Barunawaty Yunus (DiscoverSys Inc., 2009)
Radiography as diagnostic tool is essential for treatment plan of implant. Manytechniques used to produce radiography are recommended to support the dentist inaccessing area of implantation. Many implant experts use panoramic radiography asguidelines of jaw bone evaluation as recommended by implant procedures. In orderto get optimal measurement, occlusal radiography technique can be added to evaluatethe bone thickness.panoramic and periapical radiography can solely evaluate thewidth and height of jaw bone. This study proposed to evaluate parametric value, aswidth, height, and thickness of jaw bone by conventional dental diagnosticradiography. This was observational study, with cross sectional design. Samples werechosen as population target that fulfilled samples criteria. Number of samples were 30and and analyzed using the SPSS program for Windows 14.0 and T-test. In this study,it can be concluded that there was significant difference before and after conversion ofall parametric radiography conventional tooth on jaw bone.